Spatial assessment of soil erosion using the revised universal soil loss equation (RUSLE) model for sustainable marine ecosystems in the coastal of northern part, Aceh Province - Nanda Muhammad; Alwan Muhammad; Ghufran Muhammad; Fahlefy M. Iqbal Ichsan; Husein Ismail; Haridhi Haekal Azief; Munir Badrul; Sari Intan Mulia; Asyqari Amir; Hasyem Tarmizi; Muhammad Muhammad; Permatasari Indah; et al. (BIO Web of Conferences)
Coastal erosion presents a significant danger to sustainable marine ecosystems, especially in the northern coastal area of Aceh Province, Indonesia. This research combines the Revised Universal Soil Loss Equation (RUSLE) model with GIS and remote sensing to provide an innovative spatial evaluation of soil erosion risks. This study produces high-resolution maps of erosion risk and sediment yield by integrating precipitation patterns, soil properties, topography, and land use data. The results indicate substantial areas of soil erosion that contribute to sediment accumulation in coastal regions, which may affect marine ecosystems and increase land-sea connectivity issues. This methodology enhances the utilization of RUSLE in coastal environments and offers practical guidance for erosion mitigation and sustainable land management. The study highlights the significance of mitigating soil erosion as an important factor in attaining SDG 14 (Life Below Water), emphasizing the necessity for integrated policies to reduce land degradation and its subsequent effects on marine ecosystems. The findings highlight the significance of geospatial tools to encourage evidence- based decision-making for sustainable management of coastal and marine resources.